Hydrolytic Conversion of a Metal-Organic Polyhedron into a Metal-Organic Framework - Mallick, Arijit; Garai, Bikash; Díaz, David Díaz; Banerjee, Rahul (Angewandte Chemie International Edition, 2013)
Twist and release: The metal–organic polyhedron 1 synthesized from 5‐(prop‐2‐ynyloxy)isophthalic acid and Cu(NO3)2⋅ 3 H2O has a hydrophobic outer surface and a hydrophilic inner core. In an aqueous medium, the resulting polarity gradient led to the transformation of 1 into the 2D metal–organic framework 2. This unique phenomenon enabled the gradual release of entrapped drug molecules.